2015
DOI: 10.1007/s40089-015-0167-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficient FeCl3/SiO2 as heterogeneous nanocatalysis for the synthesis of benzimidazoles under mild conditions

Abstract: Iron(III) supported on nano silica as a new catalyst has been synthesized. Structural properties of this complex have been studied by TEM, SEM and EDX. The average crystalline size of Iron(III) supported on nano silica is 30-50 nm. Catalytic activity of this catalyst has been investigated by synthesis of benzimidazoles from 1, 2-diaminobenzene and aromatic aldehydes, and also the other variables investigated such as the amount of catalyst, reaction temperature and the effect of various solvents are also studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…To get the best optimum condition for the synthesis of a library of benzimidazole derivatives, the effect of the presence of inert gas or any other solvents was also examined and it was found that the maximum yield of the product was obtained when the reaction was carried out under solvent-free condition (Scheme 1B). The nanocatalyst was more effective than other heterogeneous catalysts giving a high yield of the products [17].…”
Section: Silica-supported Inorganic Salt Catalystsmentioning
confidence: 95%
“…To get the best optimum condition for the synthesis of a library of benzimidazole derivatives, the effect of the presence of inert gas or any other solvents was also examined and it was found that the maximum yield of the product was obtained when the reaction was carried out under solvent-free condition (Scheme 1B). The nanocatalyst was more effective than other heterogeneous catalysts giving a high yield of the products [17].…”
Section: Silica-supported Inorganic Salt Catalystsmentioning
confidence: 95%
“…Another new nanocatalyst, FeCl 3 ‐SiO 2 , was used by Taher et al . to synthesize the said compounds . The reaction was neat, and the reactants were heated with catalyst and hydrogen peroxide at 75°C that gave 80–96% yield of benzimidazoles in 4–10 min (Scheme , Table , entry 5).…”
Section: Nano‐transition Metal Catalyzed Oxidative Coupling Of O‐phenmentioning
confidence: 99%
“…[17] Herein, the catalyst plays a crucial role. Thus far, a variety of catalytic systems involve acidic ionic liquid, [18] organic acid (TsOHÀ SiO 2 [19] ), Lewis acids (FeCl 3 À SiO 2 , [20] CdCl 2 [21] ), metal oxide (CuO, [22] MnO 2 ), metal trifluoride (Zn(OTf) 2 , [23] In(OTf) 3 [24] ) and some organic compounds such as IBD, [25] etc.. Although some catalysts are effective, their complicated separation, purification and recycling problems severely limit their application in industry.…”
Section: Introductionmentioning
confidence: 99%